2019
DOI: 10.1080/21623945.2019.1569447
|View full text |Cite
|
Sign up to set email alerts
|

Leptin stimulates autophagy/lysosome-related degradation of long-lived proteins in adipocytes

Abstract: Obesity, a condition most commonly associated with hyper-leptinemia, is also characterized by increased expression of autophagy genes and likely autophagic activity in human adipose tissue (AT). Indeed, circulating leptin levels were previously shown to positively associate with the expression levels of autophagy genes such as Autophagy related gene-5 (ATG5). Here we hypothesized that leptin acts in an autocrine-paracrine manner to increase autophagy in two major AT cell populations, adipocytes and macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…As for the mechanism behind this phenomenon, our study shows that leptin lowers the lysosomal pH by increasing the proton-pump v-ATPase activity and promotes lysosomal degradation of autophagolysosome in a primary cilia-dependent manner. In line with our findings, leptin activates autophagy in non-neuronal cells and cancer cells 50 , 51 and stimulates the autophagy/lysosome-mediated degradation of long-lived proteins in adipocytes 50 . Early postnatal leptin replacement completely reversed the short cilia phenotype, lysosomal dysfunction, and disruption of POMC neural circuits in the hypothalamus of ob/ob mice.…”
Section: Discussionsupporting
confidence: 92%
“…As for the mechanism behind this phenomenon, our study shows that leptin lowers the lysosomal pH by increasing the proton-pump v-ATPase activity and promotes lysosomal degradation of autophagolysosome in a primary cilia-dependent manner. In line with our findings, leptin activates autophagy in non-neuronal cells and cancer cells 50 , 51 and stimulates the autophagy/lysosome-mediated degradation of long-lived proteins in adipocytes 50 . Early postnatal leptin replacement completely reversed the short cilia phenotype, lysosomal dysfunction, and disruption of POMC neural circuits in the hypothalamus of ob/ob mice.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, mice with specific deletion of Atg7 in AgRP neurons showed reduced food intake and body fat, as well as a long term effect on energy homeostasis, suggesting improvement in leptin sensitivity [ 117 ]. Notably, a recent study indicated that leptin may contribute to the dysregulated/activated adipocyte autophagy and to its dysfunction in obesity [ 118 ].…”
Section: Leptin Resistancementioning
confidence: 99%
“…This would suggest that there is a reduction in adipocyte-mediated macrophage recruitment in conditions of deficient autophagy. Illustrating a reciprocal cellular crosstalk between cytokines and autophagy, the adipokine leptin moderately enhanced autophagosome dynamics in cultured adipocytes (Goldstein et al, 2019). This finding is of particular interest, as leptin is considered and insulin sensitizing adipokine (Amitani et al, 2013) and therefore future work should examine whether leptin mediated changes in autophagy contribute to its whole-body insulin sensitizing actions.…”
Section: Autophagy and Metabolism In Human Adipose Tissuementioning
confidence: 92%